Familial Multiple Cavernous Malformation Syndrome: MR Features in This Uncommon but Silent Threat - Marc Mespreuve; Filip Vanhoenacker; Marc Lemmerling (Journal of the Belgian Society of Radiology, 2016)
Cerebral cavernous malformations (CCM) are vascular malformations in the brain and spinal cord. The familial form of cerebral cavernous malformation (FCCM) is uncommon. This autosomal dominant pathology mostly presents with seizures and focal neurological symptoms. Many persons affected by FCCM remain asymptomatic. However, acute hemorrhages may appear over time. MRI demonstrates multiple focal regions of susceptibility induced signal loss, well seen on gradient-echo sequences (GRE) or even better on susceptibility-weighted imaging (SWI). The presence of a single CCM – especially in young persons – without history of FCCM does not exclude this diagnosis. Some clinicians also advise an MRI of the spinal cord at the time of diagnosis to serve as a baseline and a control MRI of the brain every one to two years. MRI is certainly indicated in individuals with obvious new neurologic symptoms. Symptomatic siblings should also undergo an MRI of the brain to determine presence, size, and location of the lesions. Even in asymptomatic siblings, a screening MRI may be considered, as there may be an increased risk of hemorrhage, spontaneous or due to the use of certain medications; the knowledge of the presence and the type of these lesions are important. Surgical removal of a CCM may be justified to prevent a life-threatening hemorrhage. Control MRI may reveal the postoperative outcome.